SINTESIS ZEOLIT A DARI ABU DASAR BATUBARA (COAL BOTTOM ASH) DENGAN METODE PELEBURAN DAN HIDROTERMAL - Sunarti Sunarti (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2021)
Zeolites can be synthesized from materials containing silica (SiO2) and alumina (Al2O3). The analysis showed that the coal bottom ash from PLTU Paiton contained a number of oxides, namely: SiO2 49.73%; Al2O3 19.51%; Fe2O3 16.18%; CaO 5.40%; MgO 2.96%; Na2O 1.23%; K2O 0.84%; TiO2 0.99%; MnO 0.17%; and LOI of 2.38%. Zeolite from coal bottom ash was carried out by fussion and hydrothermal methods. Based on the percentage of alumina from the bottom ash, it is necessary to add pure alumina for the perfection of the zeolite formed. The addition of 1.5 g sodium aluminate resulted in a higher crystallinity level of the zeolite. This is indicated by the appearance of sharp peaks at 2Î¸ = 30.098 (d = 2.96); 24.14 (d = 3.68); 27.24 (d = 3.27); 6.63 (d = 13.31); 7.08 (d = 12.47); 7.32 (d = 12.06) and 10.30 (d = 8.58). Based on the comparison of the peaks that appear on the diffractogram with the standards proposed by Ballmoos, with the addition of 1.5 grams of aluminate, the overall zeolite formed is zeolite A.